Transformasi Ritual Aliran Sempalan Terhadap Islam di Kelurahan Tegal Sari Mandala III, Lingkungan XIII, Kecamatan Medan Denai - Andriani, Annisa Ulfa; Harahap, Indra (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2025)
This study aims to analyze the transformation of splinter sect rituals towards Islamic teachings in Tegal Sari Mandala III Village, Neighborhood XIII, Medan Denai District, based on the perspective and reports from the local community. The emergence of various religious sects by some people is considered splinter often raises questions related to ritual practices that differ from the understanding of mainstream Islam. The focus of this study is to identify how the local community observes, understands, and interprets forms of ritual transformation, factors that according to the community's perspective underlie the transformation, and the community's response to socio-religious life in Neighborhood XIII as perceived by residents. The research method used is qualitative with a case study approach. Data collection was carried out through observation of phenomena that appeared in the community and indepth interviews exclusively with various elements of the local community in Neighborhood XIII. It should be noted that adherents of the splinter sect who were the object of discussion were not interviewed directly in this study. The results of the study are expected to map the community's description of specific ritual forms that are considered to have undergone transformation, and how the community (not adherents of the sect) interpret and respond to the transformation within the framework of their understanding of Islam. Furthermore, this study will examine how perceptions of this ritual transformation affect social interactions and potential religious dynamics in the region from the perspective of the general public.